An ideological analysis of sustainable careers: identifying the role of fantasy and a way forward. Issue 1 (21st December 2020) - Bal, P. Matthijs; Matthews, Lee; Dóci, Edina; McCarthy, Lucy P.
Abstract : Purpose: Scholarly and general interest in sustainable careers is flourishing. Sustainable careers are focused on the long-term opportunities and experiences of workers across dynamic employment situations, and are characterized by flexibility, meaning and individual agency. The current paper analyzes and challenges the underlying ideological assumptions of how sustainable careers are conceptualized and advocates the inclusion of the ecological meaning of sustainability and the notion of dignity into the sustainable careers concept. Design/methodology/approach: Using Slavoj Žižek's (1989, 2001) conceptualization of ideology as fantasy-construction, the authors explore how the use of sustainable careers is influenced by fantasies about the contemporary workplace and the role of the individual in the workplace. This is a conceptual method. Findings: The authors argue that the concept of sustainable careers is grounded in the neoliberal fantasy of the individual. The paper concludes by presenting an alternative concept of sustainable careers grounded in a dignity-perspective on sustainability, which offers an alternative theoretical understanding of sustainable careers in the contemporary workplace, sharpening its contours and usefulness in theorizing careers. Originality/value: This paper is the first to systematically analyze the use and conceptualization of sustainable careers in the literate and to expose the ideological underpinnings of the concept. Propositions are developed to be explored by future research.